Inside the brush: partition by molecular weight in grafting to reactions from melt. Issue 45 (8th November 2021) - Antonioli, Diego; Chiarcos, Riccardo; Gianotti, Valentina; Terragno, Margherita; Laus, Michele; Munaò, Gianmarco; Milano, Giuseppe; De Nicola, Antonio; Perego, Michele
Abstract : A substantial partition by molecular weight takes place during the grafting to reactions. Abstract : Blends with different compositions of a partly deuterated hydroxy terminated poly(styrene d8 - st -methyl methacrylate) copolymer with average molecular weight ( M n ) of 11 200 g mol −1 and a hydroxy terminated poly(styrene- st -methyl methacrylate) copolymer with M n = 5400 g mol −1 were grafted to a silicon wafer at temperatures ranging from 170 to 250 °C. A partition according to the molecular weight takes place during the " grafting to " reaction in which the lower molecular weight component is selectively incorporated into the polymeric brush. The time and temperature evolution of the layer composition for a specific blend composition as well as the effect of the blend composition on the final brush layer composition were systematically investigated. Hybrid particle-field simulations suggest that the propensity of short chains to preferentially react with the silicon surface comes from a combination of the average number of chains in contact with silica and the substrate surface area occupied by a single chain.